Bowhead and white whale migration, distribution, and abundance in the Bering, Chukchi, and Beaufort Seas, 1975-78 - Braham, Howard W.; Krogman, Bruce D.; Carroll, Geoffrey M. (U.S. Department of Commerce, 1984)
From September 1975 to September 1977 we conducted field research on bowhead, Balaena mysticetus, and white, Delphinapterus leucas, whales in the U.S. Bering, Chukchi, and Beaufort Seas. The objectives were to determine the general distribution and migration of these whales in spring and autumn and to estimate abundance. We also surveyed the literature beginning in June 1975 through March 1978 to augment our empirical results. (PDF contains 48 pages)